Faunistic study on scorpions and their health impact in Bashagard County, Hormozgan Province, Southern Iran - Mehran Shahi; Seyed Aghil Jaberhashemi; Ahmad Ali Hanafi-Bojd; Morteza Akbari; Javad Rafinejad (Smujo International, 2021)
Abstract. Shahi M, Jaberhashemi SA, Hanafi-Bojd AA, Akbari M, Rafinejad J. 2021. Faunistic study on scorpions and their health impact in Bashagard County, Hormozgan Province, Southern Iran. Nusantara Bioscience 13: 85-90. Scorpion sting is a major public health problem in tropical and subtropical countries, endangering thousands of lives annually. About 2300 scorpion sting cases including several deaths are reported from Hormozgan Province annually. This study aimed to determine the fauna of scorpions and epidemiological aspects of scorpion sting in one of the high-risk areas in this province. Scorpions were collected by diurnal searching and night catch using UV light during 2015-2016. Clinical and demographic data of scorpion sting were obtained from Hormozgan Health Center using the checklist of the Center for Disease Control (CDC) archive during the study period. Data analysis was performed using SPSS 21 software. A total of 382 scorpions comprising of 9 species belonging to Buthidae (76%) and Hemiscorpiidae (24%) families were collected and identified as Mesobuthus phillipsi, Androctonus crassicauda, Hottentotta sistanensis, Compsobuthus persicus, Hemiscorpius acanthocercus, Orthochirus farzanpayi, H. acanthocercus, and Odontobuthos sp. The most abundant species in the study area was M. phillipsi. During 2015-2016, a total of 1221 scorpion sting cases including four deaths were recorded in Bashagard County, while most of the cases occurring during summer. The climate of the eastern regions of Hormozgan Province provides a suitable habitat for one of the deadliest genera of scorpions, i.e. Hemiscorpius. This genus is the main cause of death due to scorpion sting in these regions. It is thus necessary to design appropriate programs for the prevention and treatment of scorpion sting, including health education programs for both community members and healthcare personnel.